Healthcare utilization in the departments of obstetrics and gynecology during the first two years of the COVID-19 pandemic: time series analysis in Jining, China - Yao He; Hong Xiao; Fang Liu; Xiaochen Dai; Hongyan Wang; Haomin Yang; Zhenhui Liu; Joseph M. Unger (BMC Public Health)
Abstract Introduction Healthcare utilization in China decreased precipitously during the initial outbreak of the COVID-19 pandemic, and women were disproportionately affected. As the COVID-19 pandemic has proven to be far more pervasive and persistent than many first surmised, a vital question is whether the utilization of non-COVID related healthcare has remained low under China’s dynamic zero-COVID policy. This study aimed to estimate the initial and enduring collateral effects of the COVID-19 pandemic on the utilization of obstetrics and gynecology care at a tertiary hospital in Jining, Shandong Province, China. Methods An interrupted time series analysis was conducted to estimate the impact of the COVID-19 pandemic and mobility restrictions on monthly counts of outpatient visits, inpatient admissions, and surgeries in the obstetrics and gynecology departments at a tertiary hospital in Jining, China. Outpatient visits and surgery volume were abstracted from the hospital’s monthly healthcare delivery report, while inpatient admissions were obtained from de-identified individual electronic medical records of inpatients admitted between January 1, 2017 to December 31, 2021. Incidence Rate Ratios (IRRs) representing monthly service counts compared with counterfactual counts (had the pandemic not happened) and the volume (number) of patients lost due to the pandemic were estimated. Results During the study period, there were a total of 1 181 120 outpatient visits, 89 550 inpatient admissions and 49 056 surgeries in the obstetrics department; and 847 124 outpatient visits, 42 644 inpatient admissions and 39 653 surgeries of these totals occurred in the gynecology department. Compared to the expected estimates had the pandemic not occurred, a 55.4% (95% CI: 52.6-57.9%; p < 0.001), 31.1% (95% CI: 27.2 − 34.7%; p < 0.001), and 27.6% (95% CI: 23.2- 31.8%; p < 0.001) decrease was observed in obstetric outpatient visits, inpatient admissions, and surgeries, respectively in the month of February 2020 when the lockdown was enforced; and a 87.4% (95% CI: 86.0 − 88.4%; p < 0.001), 74.6% (95% CI: 71.0 -79.2%; p < 0.001), and 75.5% (95% CI: 70.9 − 77.8%; p < 0.001) decrease was observed in gynecologic outpatient visits, inpatient admissions, and surgeries, respectively. As of December 2021, outpatient (IRR = 0.86; 95% CI: 0.80–0.94; p < 0.001), surgery (IRR = 0.88; 95% CI: 0.82–0.95; p < 0.001), and inpatient (IRR = 0.73; 95% CI: 0.68–0.79; p < 0.0001) services in the obstetrics department, and outpatient visits (IRR = 0.90; 95% CI: 0.82–0.89; p = 0.007) in the gynecology department had not fully recovered to pre-pandemic levels. Rural residents experienced a larger immediate decrease in inpatient care utilization in both obstetrics and gynecology in the month of February 2020, and the return to pre-pandemic levels in care utilization was also slower than that of urban residents. Conclusions The COVID-19 pandemic led to sizable disruptions in routine delivery and utilization of obstetrics and gynecology care. Disruptions were particularly substantial during the initial wave of the outbreak, and full recovery to pre-pandemic levels has not yet been achieved. The impact was more dramatic for women from rural areas, highlighting the need for policies and programs that address inequities in pandemic response and preparedness.